2003
DOI: 10.1093/jrs/16.4.398
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Integration Policy and Experiences of Settlement: A Case Study of Refugees in Rome

Abstract: This article examines the question of an absence of an integration policy, and specifically how this lack of state intervention is perceived by refugees themselves, and how it shapes their attitudes towards and strategies for integration. The emphasis in examining integration of refugees in this paper is on the importance of human agency in the process of structuring and re-structuring social relations across space and time. The article is based upon research among a group of refugees from former Yugoslavia se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…In other words, the experience of discrimination at different levels (personal vs. group) will always have negative effects and result in different adaptation outcomes, depending on the level at which discrimination is experienced. Previous literature has also shown that direct personal experience with discrimination usually results in higher acculturative stress (Korac, 2003;Lueck & Wilson, 2010), and perceived group discrimination usually results in the rejection of national identity (Ruggiero et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In other words, the experience of discrimination at different levels (personal vs. group) will always have negative effects and result in different adaptation outcomes, depending on the level at which discrimination is experienced. Previous literature has also shown that direct personal experience with discrimination usually results in higher acculturative stress (Korac, 2003;Lueck & Wilson, 2010), and perceived group discrimination usually results in the rejection of national identity (Ruggiero et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Korac (2003) suggests that citizenship allows formal entry into a host community, and guarantees the newcomers basic civil, political, economic, social, and cultural rights provided by the host country. These immigration policies were developed to ensure the success of immigrants (Esses et al, 2001).…”
Section: Bosnian Refugees In St Louismentioning
confidence: 99%
“…This process is necessary both for initial survival as well as the longer-term process of integration into a host country (e.g., Berry, 1992;Breslow et al, 1997;Korac, 2003). On the individual and programmatic levels, social support has been found to be a key element in ensuring refugees' well-being in resettlement (e.g., Beiser & Johnson, 2003;Breslow et al, 1997;Ives, 2007;Rousseau, Drapeau, & Corin, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, Breslow and colleagues (1997) and Ives (2005Ives ( , 2007 found sponsorship vital to refugee resettlement outcomes: refugees who had congregation-affiliated sponsors had greater opportunities for upward mobility, higher-than-minimum-wage income, and employment benefits such as adequate health care coverage and retirement plans. Resettlement research examining refugee employment in Canada (e.g., Krahn, Derwing, Mulder & Wilkinson, 2000), Italy (Korac, 2003), the UK (Duke, 1996), and the United States (Ives, 2005(Ives, , 2007Takeda, 2000) indicates that unless there is some mediation, most refugees who arrive with little to no English proficiency will end up in no-or low-skill, low-wage labor from which there is little upward mobility.…”
Section: Congregational Participation In Contextmentioning
confidence: 99%
See 1 more Smart Citation